Expanding HTA - Correcting a Misattribution, Clarifying the Scope of HTA and CEA; Comment on "Ethics in HTA: Examining the 'Need for Expansion'" - Anthony J. Culyer (Kerman University of Medical Sciences, 2019)
Abrishami, Oortwijn, and Hofman (AOH) attribute to me a position I do not hold and an argument I did not make. The purpose of this note is make clear what my position actually is and to clarify the main differences between health technology assessment (HTA) and cost-effectiveness analysis (CEA).